Performance and sizing of filtration equipment to replace mineral fertilizer with digestate in drip and sprinkler fertigation. (1st October 2021) - Finzi, Alberto; Guido, Viviana; Riva, Elisabetta; Ferrari, Omar; Quilez, Dolores; Herrero, Eva; Provolo, Giorgio
Abstract: Fertigation offers a practicable solution for applying digestate according to crop requirements during the growing season. Digestate injection in irrigation water can enhance the nutrient use efficiency, but a proper solid–liquid separation system is required to avoid nozzle clogging of drippers or sprinklers. To develop knowledge about the performance of filtration systems making fertigation with digestate feasible in a wider context, four different full-scale filtration systems (one microfilter with a screen size of 50 μm and three vibrating screens with screen sizes of 100, 200 and 500 μm) in farms equipped with driplines or center pivots were evaluated. Filtration system performance was evaluated based on a mass balance, electricity consumption, and a separation index for solids, nitrogen, ammonia, phosphorus, and potassium. Performance depended on type of separator, initial total solids content of digestate, screen size, and input flow rate. The separation index ranged from 25% to 84% for solids, and from 7% to 79% for nutrients. Starting from these performance, a sizing procedure to design a filtration system and optimize digestate's nutrients supply with fertigation was developed. In general, adequate filtered digestate flow rates of 0.8–7.1 m3/h and dilution ratio of 4–10% can be considered. Based on agronomic conditions, digestate composition and irrigation system features, an example design to apply 140 kg/ha of nitrogen during the maize irrigation season is proposed. The correct selection and sizing of the filtration equipment can contribute to the implementation of a sustainable practice for enhanced use of digestate as fertilizer. Graphical abstract: Image 1 Highlights: Fertigation is a feasible solution to apply digestate according to crop requirements. Separation systems with vibrating screen and microfilter were tested at four farms. Separation index ranged from 25% to 84% for solids and from 7% to 79% for nutrients. A sizing procedure was developed to design an optimize filtration system.